Effect of matric suction and density on yield stress, compression index and collapse potential of unsaturated granite soil - Kholghifard, M. (Springer Verlag, 2021)
Residual granite soil from Malaysia shows some problematic features such as: high void ratio, low natural dry density, and loose of apparent cohesion of the soil immediately after rain due to wetting. This study is aimed to evaluate the influence of suction and density on unsaturated behavior of the residual granite soil e.g., the yield stress (σc), compression and swelling indices (Cc, Cr), and collapse potential (CP). To do that, a modified oedometer was fabricated on the basis of the axis translation technique (ATT). Then, one-dimensional consolidation tests were performed under different suctions using the modified oedometer. The results showed a negligible increase in σc when the applied suctions were less than the air entry value. The σc values of dense soil samples were higher than that of loose soil samples regardless of the matric suction. Besides, the values of Cc appeared in three zones: saturation, desaturation and residual zones, while, Cr was independent of the matric suction. The difference of CP under similar matric suction indicated a hydraulic hysteresis behavior of the residual granite soil. However, the hydraulic hysteresis effect on the maximum CP was negligible.